Learning to teach history in the secondary school : a companion to school experience - Haydn, Terry, 1951- (Routledge, 1997)
Introduction. The place of history in the school curriculum. Planning for learning: learning objectives. Learning strategies and the use of language. Developing historical understanding. Pupils with special educational needs in the history classroom. The use of new technology in the history classroom. The use of resources in the teaching of history. Assessment in the classroom. Teaching for external examinations. Continuing professional development.